Einfluss der Belastungsdauer beim HIT-Krafttraining - Gail, S.; Maier, S.; Künzell, S. (Sports & exercise medicine switzerland, 2019)
High intensity training (HIT) is a variant of single-set training. It is becoming increasingly popular in strength training practice. Contrary to the large number of research on multiple-set training, empirical investigations addressing HIT are rare. There is evidence that an important factor for muscle hypertrophy is the muscle time under tension (TUT). However, scientific knowledge about the optimal length of the TUT is lacking. Therefore, the aim of the present study was to compare the effects of a rather short TUT (20-40 s) with a rather long TUT (50-70 s) during HIT strength training. Nine experienced recreational sportsmen completed a ten week HIT strength training either with the short or the long TUT. The participants performed a whole-body training program with nine strength exercises twice a week. After the intervention they showed significant improvements of 5-RM (p < 0.05; 0.780 = ?2 = 0.906) for all strength exercises. The short TUT intervention group increased their strength performance by 20.6%-44.2%, whereas the long TUT intervention group improved by 12.3%-33.7%. There were no statistically significant differences between both intervention groups (p > 0.05; 0.007 = Eta2 = 0.340). With respect to body composition, the participants increased their body weight from pre- to posttest (p < 0.05; Eta2 = 0.515), which could be explained by the significant growth of muscle mass (p < 0.05; Eta2 = 0.634). Statistically significant differences between both intervention groups were not found for any of the investigated body composition parameters (p > 0.05; 0.039 = Eta2 = 0.123). In conclusion, the study verifies the high effectiveness of HIT strength training. Moreover, the results indicate that the TUT within a HIT strength training has no practically relevant effect, if the TUT amounts between 20-70?s until first concentric muscle failure.